Examination of the Potential for Adaptive Chirality of the Nitrogen Chiral Center in Aza-Aspartame - Bouayad-Gervais, Samir H. (Molecules, 2013)
The potential for dynamic chirality of an azapeptide nitrogen was examined by substitution of nitrogen for the α-carbon of the aspartate residue in the sweetener S,S-aspartame. Considering that S,S- and R,S-aspartame possess sweet and bitter tastes, respectively, a bitter-sweet taste of aza-aspartame 9 could be indicative of a low isomerization barrier for nitrogen chirality inter-conversion. Aza-aspartame 9 was synthesized by a combination of hydrazine and peptide chemistry. Crystallization of 9 indicated a R,S-configuration in the solid state; however, the aza-residue chiral center was considerably flattened relative to its natural amino acid counterpart. On tasting, the authors considered aza-aspartame 9 to be slightly bitter or tasteless. The lack of bitter sweet taste of aza-aspartame 9 may be due to flattening from sp(2) hybridization in the urea as well as a high barrier for sp(3) nitrogen inter-conversion, both of which may interfere with recognition by taste receptors.